The effectiveness of botulinum toxin on spasticity and gait of hemiplegic patients after stroke: A systematic review and meta-analysis. (November 2021) - Varvarousis, Dimitrios N; Martzivanou, Christina; Dimopoulos, Dimitris; Dimakopoulos, Georgios; Vasileiadis, George I.; Ploumis, Avraam
Abstract: The aim of the study is to evaluate the evidence supporting the efficacy of botulinum toxin type A (BTA) injections in lower limb of hemiplegic patients, after stroke or cerebrovascular accident, and their gait analysis. This study included: randomized controlled trials (RCTs), non-randomized or controlled clinical trials (CCTs) or cluster trials, clinical trials of various phases (I-III), interrupted time series (ITS) studies with at least three data points before and after the intervention, controlled before and after (CBA) studies, prospective and retrospective comparative cohort studies, case-control and multicentred studies. The patients included in these studies had similar characteristics: age over 18 years, history of stroke and following hemiplegia, minimum modified Ashworth scale (MAS) score of 2 and duration since stroke over 6 months. The number of studies included in this review was 21. A meta-analysis was performed on a fraction of them depending on the reported index and the methodology as reported in detail in the results section. MAS score, following BTA injections, was significantly improved (Hedges' g: −1.17; 95% CI: −1.66, 0.67; p < 0.001). The same applied for the 10 Meter Walk Test (MWT) (−0.35; 95% CI: −0.68, −0.02; p = 0.016). The gait velocity showed improvement, yet without statistical significance (0.27; 95% CI: −0.09, 0.63; p = 0.285). We concluded that botulinum toxin injections showed effectiveness on lower limb hypertonia reduction of hemiplegic patients after stroke. Apart from significantly reducing the MAS scores, 10 MWT was also improved. However, more research is required in order to determine the advancement in specific gait and posture parameters. Highlights: Our review showed that BTA injections reduce spasticity and improve the gait indices of post-stroke patients. The aforementioned improvement of spasticity and gait using the MAS and 10 MWT was statistically significant. Even though an increase of gait velocity was also observed, it did not reach statistical significance.